Massively parallel sequencing techniques for forensics: A review - Bruijns, Brigitte (Electrophoresis, 2018)
DNA sequencing, starting with Sanger's chain termination method in 1977 and evolving into the next generation sequencing (NGS) techniques of today that employ massively parallel sequencing (MPS), has become essential in application areas such as biotechnology, virology, and medical diagnostics. Reflected by the growing number of articles published over the last 2–3 years, these techniques have also gained attention in the forensic field. This review contains a brief description of first, second, and third generation sequencing techniques, and focuses on the recent developments in human DNA analysis applicable in the forensic field. Relevance to the forensic analysis is that besides generation of standard STR‐profiles, DNA repeats can also be sequenced to look for polymorphisms. Furthermore, additional SNPs can be sequenced to acquire information on ancestry, paternity or phenotype. The current MPS systems are also very helpful in cases where only a limited amount of DNA or highly degraded DNA has been secured from a crime scene. If enough autosomal DNA is not present, mitochondrial DNA can be sequenced for maternal lineage analysis. These developments clearly demonstrate that the use of NGS will grow into an indispensable tool for forensic science.